Microsurgical testicular denervation for the treatment of chronic testicular pain initial results - Oliveira, Rafael Garcia de (2009)
INTRODUCTION: Chronic testicular pain remains an important challenge for urologists. Currently, the treatment plan is primarily empirical, with the first approach consisting of clinical measures. However, some patients remain in pain despite a conservative treatment protocol and, for them, it is possible to perform a surgical procedure that involves severing the scrotal and spermatic branches of the genitofemoral and ilioinguinal nerve fibers. METHODS: In our institution, 60 patients were evaluated and treated for idiopathic chronic testicular pain between January 2003 and July 2007. Priority was give to clinical treatment, which evolved from simple to more complex measures. Microsurgical treatment was performed on those who experienced no considerable pain relief (10 individuals in our study). RESULTS: Over a twenty-four-month follow-up period, 70% of patients showed complete remission and 20% exhibited partial relief from pain.